WNT10A rs147680216 G>A mutation indicates a higher risk for non-syndromic oral cleft in a northeastern Chinese population. Issue 6 (July 2019) - Feng, C.; Wang, Q.; Cao, Z.; Guan, H.; Xu, Z.-F.
Abstract: Non-syndromic oral cleft lip and palate is a heterogeneous group of congenital malformations that consist of cleft palate, and cleft lip with or without cleft palate. The members of the wingless type mouse mammary tumour virus (MMTV) integration site family (Wnts) regulate various developmental processes including craniofacial development, and have a role in that of cleft lip and palate. We aimed to identify the potential polymorphisms in the Wnt10a gene, and to explore the association between the variations in the gene and the risk of development of cleft palate. A total of 198 affected patients (cleft lip, n = 67; cleft palate, n = 48; and both, n = 83) together with 187 healthy controls were enrolled (all from the Chinese Han population in NE China). A fragment of 316 bp was amplified from the blood genome of each participant by polymerase chain reaction (PCR) using specific primers that targeted the Homo sapiens Wnt10a gene. By using the restriction enzyme AluI, the population analysed were classified into three genotypes, GG (316 bp), GA (316 bp, 117bp, 199bp) and AA (117bp, 199bp) based on the rs147680216 G/A polymorphism (Gly>Ser mutation at position 213 of Wnt10a protein) of theWnt10a gene. The frequency of allele A in the affected group was significantly higher (14.1% compared with 3.2% in the control group). The allele G with an odds ratio (OR) of 0.201 and 95% CI of 0.445 to 0.091 was not a risk factor for the condition in the affected group. However, the distribution of the genotype did affect its occurrence in the affected group (p < 0.001 ), but not the classification of types (p = 0.901). In conclusion we found an rs147680216 G>A mutation that was associated with non-syndromic cleft lip and palate in the Wnt10a gene.